The Potential of Developing Computational Thinking Approach-Based Physics Learning Media as a Means of Increasing Students' Problem-Solving Ability - Dwiyanti, Ulfa; Al-Qoyyim, Thufail Mujaddid; Diarta, Muhamad Hendri; Jaswadi, Jaswadi (AMPLITUDO : Journal of Science and Technology Innovation, 2023)
A computational thinking approach is an approach to thinking and reasoning by computer scientists. Computational thinking skills can be adopted as an approach to solving a problem and analyzing the solution. The computational thinking approach is not limited to computer science but can also be applied to other disciplines through problem-solving. The computational thinking approach has been integrated into various instruments and learning media. The purpose of this research is to see the potential of the computational thinking approach to be integrated into learning media to improve problem-solving skills and to discuss the integration of computational thinking in various learning tools and media. This research method uses literature studies with 6 international articles as the main source from scopus.com and 19 articles as supporting articles from scholar.google.com. The results of the study show that the computational thinking approach has the potential to be integrated into various learning tools and media as a means of increasing problem-solving skills.